Different responses of soil element contents and their stoichiometry (C: N: P) to different grazing intensity on the Tibetan Plateau shrublands - Nie, Xiuqing; Li, Changbin; Ren, Lining; Chen, Yongzhe; Du, Yangong; Li, Xilai; Wang, Dong; Zhou, Guoying (Frontiers in Environmental Science, 2023)
Potentilla fruticose, the major alpine shrubland type, is widely distributed across the Tibetan Plateau, and grazing is the most common disturbance in the shrublands of Potentilla fruticose. However, soil organic carbon (SOC), soil total nitrogen (STN), soil total phosphorus (STP), and their stoichiometry under different grazing intensities were unclear. In our study, we explored SOC, STN, STP, their stoichiometry, and their controlling factors in the grazing disturbance of heavy grazing (HG), moderate grazing (MG), light grazing (LG), and no grazing (NG) in the Tibetan Plateau P. fruticose shrublands. The grazing intensities were mainly referred by the shrublands’ ground cover, the indicators of the road density, the distance between sampling sites and cowshed or sheep shed, the amounts of cow and sheep dung, gnawing and stampeding vegetation were also referred to decide the grazing intensity. Our results indicated that soil physical properties of soil temperature and bulk density have decreasing trends with decreasing grazing intensities from HG to NG. The SOC, STN, STP, soil C: N, and C: P ratios have increasing trends with decreasing grazing intensities from HG to NG, while the changes in soil N: P ratio were relatively stable along grazing intensities. Our results indicated that HG generally had stronger effects on SOC, STN, soil C: N, and C: P ratios than NG, indicating substantial effects of grazing disturbance on biogeochemical cycles of SOC and STN in the shrubland ecosystems. Therefore, for the alpine shrubland of P. fruticose, the HG should be avoided for sustainable cycling of soil nutrients and the balance of soil nutrient stoichiometry. The grazing types can directly affect plant conditions, and plant conditions can directly affect soil physical and chemical properties and litter standing crops. Finally, soil physicochemical properties and litter standing crop resulting from different grazing intensities directly control SOC, STN, and STP. For the soil stoichiometry, the soil’s physical and chemical properties resulting from different grazing intensities have direct impacts on soil C: P and N: P ratios.